STRATEGI DIGITAL MARKETING UNTUK PENINGKATAN PENJUALAN JAJAN TRADISIONAL UMKM DI KELURAHAN MLATIBARU SEMARANG - Tri Widiastuti (Jurnal Riptek, 2021)
The purpose of this study is to analyze digital marketing strategies for traditional snack business in Mlatibaru Village, Semarang. Digital Marketing makes it easier for business actors to provide information and interact with consumers; expand market, raise awareness and increase sales. The research method uses a descriptive approach, with the stages of seeking information, reduction/focus and selection. At this stage the researcher describes the focus that has been set in more detail. The research site is in the Traditional Snack Thematic Village in Mlatibaru Village, Semarang. The informants are Mrs. Iyas, Mrs. Yasmin and Mrs. Tere, Mrs. Mudji as policy makers and Mrs. Endang and Mrs. Eni as consumers. Data collection techniques in this study through observation, interview, and document. Qualitative data analysis techniques using the Miles and Hubermans model include: data reduction, data presentation, drawing conclusions, and verifying the validity of the research data using triangulation and sources. The results of this study analyze digital marketing strategies to get consumers, build preferences, promote brands, increase sales and increase profits. The obstacles for business actors are low understanding of information technology, not maximizing e-commerce and markets, creating interesting content and influencing buyers.